Strongly enhanced colorectal cancer risk stratification by combining family history and genetic risk score - Weigl, Korbinian; Chang-Claude, Jenny; Knebel, Phillip; Hoffmeister, Michael; Brenner, Hermann (Clinical epidemiology, 2018)
Strongly enhanced colorectal cancer risk stratification by combining family history and genetic risk score Korbinian Weigl,1,2 Jenny Chang-Claude,3,4 Phillip Knebel,5 Li Hsu,6 Michael Hoffmeister,1 Hermann Brenner1,2,7 1Division of Clinical Epidemiology and Aging Research, German Cancer Research Center (DKFZ), Heidelberg, 2German Cancer Consortium (DKTK), German Cancer Research Center (DKFZ), Heidelberg, 3Unit of Genetic Epidemiology, German Cancer Research Center (DKFZ), Heidelberg, 4University Cancer Center Hamburg, University Medical Center Hamburg-Eppendorf, Hamburg, 5Department for General, Visceral and Transplantation Surgery, University Heidelberg, Heidelberg, Germany; 6Public Health Sciences Division, Fred Hutchinson Cancer Research Center, Seattle, WA, USA; 7Division of Preventive Oncology, German Cancer Research Center (DKFZ) and National Center for Tumor Diseases (NCT), Heidelberg, Germany Background and aim: Family history (FH) and genetic risk scores (GRSs) are increasingly used for risk stratification for colorectal cancer (CRC) screening. However, they were mostly considered alternatively rather than jointly. The aim of this study was to assess the potential of individual and joint risk stratification for CRC by FH and GRS.Patients and methods: A GRS was built based on the number of risk alleles in 53 previously identified single-nucleotide polymorphisms among 2,363 patients with a first diagnosis of CRC and 2,198 controls in DACHS [colorectal cancer: chances for prevention through screening], a population-based case-control study in Germany. Associations between GRS and FH with CRC risk were quantified by multiple logistic regression.Results: A total of 316 cases (13.4%) and 214 controls (9.7%) had a first-degree relative (FDR) with CRC (adjusted odds ratio [aOR] 1.86, 95% CI 1.52–2.29). A GRS in the highest decile was associated with a 3.0-fold increased risk of CRC (aOR 3.00, 95% CI 2.24–4.02) compared with the lowest decile. This association was tentatively more pronounced in older age groups. FH and GRS were essentially unrelated, and their joint consideration provided more accurate risk stratification than risk stratification based on each of the variables individually. For example, risk was 6.1-fold increased in the presence of both FH in a FDR and a GRS in the highest decile (aOR 6.14, 95% CI 3.47–10.84) compared to persons without FH and a GRS in the lowest decile.Conclusion: Both FH and the so far identified genetic variants carry essentially independent risk information and in combination provide great potential for CRC risk stratification. Keywords: colorectal neoplasms, familial risk, common genetic variants, single-nucleotide polymorphisms